2015
DOI: 10.4142/jvs.2015.16.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Elevated level of renal xanthine oxidase mRNA transcription after nephropathogenic infectious bronchitis virus infection in growing layers

Abstract: To assess relationships between xanthine oxidase (XOD) and nephropathogenic infectious bronchitis virus (NIBV) infection, 240 growing layers (35 days old) were randomly divided into two groups (infected and control) of 120 chickens each. Each chicken in the control and infected group was intranasally inoculated with 0.2 mL sterile physiological saline and virus, respectively, after which serum antioxidant parameters and renal XOD mRNA expression in growing layers were evaluated at 8, 15 and 22 days post-inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Lin et al . [ 40 ] reported that serum uric acid concentration was found higher in infected (with nephropathogenic infectious bronchitis virus) growing layers as compared to non-infected ones. Concomitant with this, serum concentration of uric acid was higher in broiler chickens fed mycotoxins [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al . [ 40 ] reported that serum uric acid concentration was found higher in infected (with nephropathogenic infectious bronchitis virus) growing layers as compared to non-infected ones. Concomitant with this, serum concentration of uric acid was higher in broiler chickens fed mycotoxins [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study (Hiromi et al, 2014) shown that the highest relative expression of cytokines correlated with the infection degree of IBV and IBV infection could provoke renal inflammatory responses (Okino et al, 2014). Our previous study found that NIBV infection induced both renal XOD transcription and its serum activity increase in growing layers, the serum concentration of UA was statistically increased (Lin et al, 2015). Earlier study showed that NIBV triggers UA salt precipitation by invading the tubule cell to initiate kidney tissue damage (Kim et al, 2006;Okino et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, determination of MDA and SOD can reflect the capability of elimination of free radicals in the body and the extent of CK cells injury during IBV infection (Zhou et al, 2006). Earlier vivo studies has proved that the kidney was vulnerable attacked by ROS (Hiromi et al, 2014) and NIBV infection could cause serum SOD activity of growing layers increased (Lin et al, 2015). The results indicated that abnormal generation of ROS might be a pathogenesis of damages in NIBV injury of CK cells, but the detailed pathogenic mechanism need to have further studies and discussions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations